The effect of neoadjuvant chemotherapy and chemoradiotherapy on exercise capacity and outcome following upper gastrointestinal cancer surgery: an observational cohort study. Issue 1 (December 2016) - West, M.; Loughney, L.; Ambler, G.; Dimitrov, B.; Kelly, J.; Mythen, M.; Sturgess, R.; Calverley, P.; Kendrick, A.; Grocott, M.; Jack, S.
Abstract Background In 2014 approximately 21, 200 patients were diagnosed with oesophageal and gastric cancer in England and Wales, of whom 37 % underwent planned curative treatments. Potentially curative surgical resection is associated with significant morbidity and mortality. For operable locally advanced disease, neoadjuvant chemotherapy (NAC) improves survival over surgery alone. However, NAC carries the risk of toxicity and is associated with a decrease in physical fitness, which may in turn influence subsequent clinical outcome. Lower levels of physical fitness are associated with worse outcome following major surgery in general and Upper Gastrointestinal Surgery (UGI) surgery in particular. Cardiopulmonary exercise testing (CPET) provides an objective assessment of physical fitness. The aim of this study is to test the hypothesis that NAC prior to upper gastrointestinal cancer surgery is associated with a decrease in physical fitness and that the magnitude of the change in physical fitness will predict mortality 1 year following surgery. Methods This study is a multi-centre, prospective, blinded, observational cohort study of participants with oesophageal and gastric cancer scheduled for neoadjuvant cancer treatment (chemo- and chemoradiotherapy) and surgery. The primary endpoints are physical fitness (oxygen uptake at lactate threshold measured using CPET) and 1-year mortality following surgery; secondary endpoints include post-operative morbidity (Post-Operative Morbidity Survey (POMS)) 5 days after surgery and patient related quality of life (EQ-5D-5 L). Discussion The principal benefits of this study, if the underlying hypothesis is correct, will be to facilitate better selection of treatments (e.g. NAC, Surgery) in patients with oesophageal or gastric cancer. It may also be possible to develop new treatments to reduce the effects of neoadjuvant cancer treatment on physical fitness. These results will contribute to the design of a large, multi-centre trial to determine whether an in-hospital exercise-training programme that increases physical fitness leads to improved overall survival. Trial registration ClinicalTrials.govNCT01325883 - 29th March 2011.